2015
DOI: 10.1063/1.4931676
|View full text |Cite
|
Sign up to set email alerts
|

Electron percolation in realistic models of carbon nanotube networks

Abstract: The influence of penetrable and curved carbon nanotubes (CNT) on the charge percolation in threedimensional disordered CNT networks have been studied with Monte-Carlo simulations. By considering carbon nanotubes as solid objects but where the overlap between their electron cloud can be controlled, we observed that the structural characteristics of networks containing lower aspect ratio CNT are highly sensitive to the degree of penetration between crossed nanotubes. Following our efficient strategy to displace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Simoneau and al. studied numerically the influence on the estimated effective resistance of the statistical distribution chosen for angles, lengths, diameters of nanowires (in that case CNTs) 11 , waviness, degree of penetration of CNTs 12 , under the junction dominated assumption (JDA) -i.e. assuming ballistic transport in individual CNTs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simoneau and al. studied numerically the influence on the estimated effective resistance of the statistical distribution chosen for angles, lengths, diameters of nanowires (in that case CNTs) 11 , waviness, degree of penetration of CNTs 12 , under the junction dominated assumption (JDA) -i.e. assuming ballistic transport in individual CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…penetration of CNTs 12 , under the junction dominated assumption (JDA) -i.e. assuming ballistic transport in individual CNTs.…”
mentioning
confidence: 99%
“…It was reported that for randomly aligned CNTs, measuring direction does not affect conductivity by too much. 20 For the bare VACNTs, multiple contact points actually existed among adjacent tubes. Thus, a complex and nondirectional conducting network formed, on which condition the conduction behavior of the electron was dominated not only by the pathways provided by individual VA CNTs but also by the intertube percolation.…”
Section: Electrical Anisotropymentioning
confidence: 99%
“…At those thicknesses, the electrical transport and resistivity in these networks deviate from their bulk properties and are governed by percolation theory (Stauffer and Aharony, 1985). As a result, Monte Carlo simulations need to be employed to theoretically calculate the percolation resistivity of networks consisting of 1D nanoelements (Jagota and Tansu, 2015;Simoneau et al, 2015;White et al, 2009;Berhan and Sastry, 2007). However, most simulation work on 1D nanoelement networks has modeled the nanowires as straight sticks.…”
Section: Introductionmentioning
confidence: 99%
“…Curviness not only affects the percolation threshold, but also the resistivity of the network, which determines the sheet resistance of transparent conductors. In a few previous studies, it has been shown that waviness decreases the conductivity of carbon nanotube networks (Simoneau et al, 2015) and three-dimensional (3D) carbon nanotube-based nanocomposites (Bao et al, 2013;Takeda et al, 2011;Li et al, 2007;Dalmas et al, 2006). However, a systematic and comprehensive study of the effect of nanowire curviness on the scaling of percolation resistivity in metal nanowire networks and its interaction with other nanowire/device parameters, in particular nanowire alignment, is currently lacking.…”
Section: Introductionmentioning
confidence: 99%